Exploring Multilingualism in Professional Context: Scientometric Analysis - Aimoldina, А.А.; Zharkynbekova, Sh.К. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
Professional multilingualism has been the subject of multiple interdisciplinary research including sociolinguistics and business communication as well as studies about the neuropsychological aspects of the multilingual brain and multilinguals’ language practices in the workplace settings. In recent years, there has been a noteworthy growth in the scholarly interests and contribution in professional multilingualism. In this research study, a bibliometric analytical technique is used to examine the concept of professional multilingualism. The purpose of this study is to analyse the bibliographical data to find the recent scenario of Scopus as well as Web of Science (WoS) core collections pertaining to professional multilingualism literature. Based on the scientometric methodology conducted in October 2022, the authors retrieved publications using the key terms like “Professional multilingualism” or “Multilingualism at work” or “Business communication”, etc. that in general extracted 3,875 scientific contributions. Therefore, the time frame considered for this study is between 1970 and 2022. The study analyses the growth of author productivity, the publication models, the distribution of the thematic category, the distribution of the author’s keywords, the country of publications, as well as the most frequently cited articles related to professional multilingualism publications and other aspects. In addition, the result identified the significant areas related to professional multilingualism focuses on Corporate Language, Multilingualism, Language Policy, Language Management, Intercultural Communication. Future research could extend a similar study in other related areas in professional language teaching-learning to explore the publication trends globally.